Chemical composition, antioxidant and antibacterial activity of essential oil from leaf of syzygium polyanthum (wight) walp. - Nur Amalina, Ahmad (2014)
Syzygium polyanthum (Wight) Walp. is a plant widely consumed as raw vegetables or used in culinary in Malaysia. This study was performed to determine the chemical composition, antioxidant and antibacterial activity of Syzygium polyanthum essential oil from Malaysia. The essential oil was extracted from the leaf by hydrodistillation method. The percentage of the essential oils obtained, for the fresh and the dried leaf were 0.67 % and 1.50 %, respectively. Analysis by GCMS revealed a total of 26 and 29 compounds, representing 71.71 % and 90.92 % of the overall compositions, were detected in the fresh and the dried leaf essential oils. Both oils were characterized by high amount of monoterpene hydrocarbons with α-pinene was the major compounds for the fresh leaf (28.78 %) and the dried leaf (34.15 %). The antioxidant activities of the fresh and dried leaf oils were evaluated using three different assay; DPPH free radical scavenging, β-carotene bleaching and ferrous-ion chelating. Results showed that the oils exhibited a potential antioxidant activity. The antibacterial activity was evaluated using the disc diffusion and microdilution methods against three gram-positive bacteria (Bacillus subtilis, Enterococcus faecalis) and three gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella typhii). The oils exhibited antibacterial activity against all of the tested bacteria. The minimum inhibitory concentration (MIC) values for the fresh leaf oil were in the range of 0.03 mg/ml to 0.25 mg/ml while the MIC values for the dried leaf oil were in the range of 0.03 mg/ml to 0.12 mg/ml. The chemical composition, antioxidant and antibacterial activity of essential oil of S. polyanthum from Malaysia is presented here for the first time